HUBUNGAN KECERDASAN KINESTETIK DAN PENGUASAAN KALIMAT EFEKTIF DENGAN KETERAMPILAN MENULIS TEKS ULASAN KARYA SISWA KELAS VIII SMPN 7 KOTA SERANG TAHUN AJARAN 2018/2019 - Asih Nofita; Aceng Hasani; Ade Husnul Mawadah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2019)
This research aims to know wheter there is relationship between kinesthetic intelligence and effective sentences mastery by students' writing ability on their review text. The research method used survey method through quantitative correlation studies. The population of this study was the eight grade of SMPN 7 Kota Serang with 346 students and the sample was 50 students by using simple random sampling. In field, data was collected by using checklist sheet such as; objective test, and subjective test for their kinesthetic intelligence and review text testing. The analysis technique used description analysis technique and analysis requirements testing by normality test, linearity test, and multicollinearity test. Hypothesis testing used a simple and multiple test. So, the result of normality test which is obtained X1 is 0,797, X2 is 1,103, and Y is 1,134. Therefore, the data was normally distributed. The linearity test showed that the result X1 and Y are 1,334 and X2 and Y are 0,474. The multicollinearity test X1 and X2 showed a tolerance values are 0,352 also VIF X1 and X2 are 2,838. Multiple significance test indicated Fcount is 38,354. Variables had a significant relationship. The result of research proved that kinesthetic intelligence was needed to help process all information including language activities and effective sentences were needed in writing activity especially the text purposed for general public such as; review text.